2018
DOI: 10.18632/oncotarget.24353
|View full text |Cite
|
Sign up to set email alerts
|

Value-based genomics

Abstract: Advancements in next-generation sequencing have greatly enhanced the development of biomarker-driven cancer therapies. The affordability and availability of next-generation sequencers have allowed for the commercialization of next-generation sequencing platforms that have found widespread use for clinical-decision making and research purposes. Despite the greater availability of tumor molecular profiling by next-generation sequencing at our doorsteps, the achievement of value-based care, or improving patient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 201 publications
1
35
0
Order By: Relevance
“…In fact, the most common concern of participants was that sequencing would not yield clinically useful findings, which seems well-justified given that precision oncology studies have not yet demonstrated general effectiveness of molecular profiling in cancer treatment. 27 Our findings should be interpreted in light of several study limitations. The study sample of cancer patients was disproportionately white and college-educated, limiting generalizability of study results.…”
Section: F I G U R Ementioning
confidence: 81%
See 1 more Smart Citation
“…In fact, the most common concern of participants was that sequencing would not yield clinically useful findings, which seems well-justified given that precision oncology studies have not yet demonstrated general effectiveness of molecular profiling in cancer treatment. 27 Our findings should be interpreted in light of several study limitations. The study sample of cancer patients was disproportionately white and college-educated, limiting generalizability of study results.…”
Section: F I G U R Ementioning
confidence: 81%
“…Although literature on the ethical, legal, and social implications of genetic testing has often highlighted the potential harms of learning personal genetic information, relatively few patients in the study expressed concerns regarding the possibility of psychological distress or unwanted information as a result of undergoing sequencing. In fact, the most common concern of participants was that sequencing would not yield clinically useful findings, which seems well‐justified given that precision oncology studies have not yet demonstrated general effectiveness of molecular profiling in cancer treatment …”
Section: Discussionmentioning
confidence: 99%
“…It is important to carefully consider the panel size and composition for accurate TMB assessment. Supporting this concept, it has been observed that confidence intervals for TMB estimation increase with the use of gene panels that assess a smaller area of the genome compared with those that assess a larger area, which suggests that using smaller coverage gene panels could lead to the overestimation or underestimation of TMB . Depth of sequencing also differs between WES and targeted gene panel assays; sequencing depth is greater for targeted gene panels (~500×) than for WES (~100×) .…”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Outputmentioning
confidence: 99%
“…47,48 To date, most of the published studies have assessed TMB in solid tumor samples; however, blood TMB assessment assays are increasingly being used to assess TMB association with response to immune checkpoint inhibitors ( Preanalytical Sample type FFPE samples may harbor artefactual deamination alterations that may impact mutation calling and TMB calculation 56,57 Tumor purity Infiltration of tumor with immune or TME cells may impact TMB score (lower tumor purity is associated with reduced sensitivity) 32 Sequencing parameters Genomic region covered TMB score will depend on panel size and genomic region covered. Greater panel sizes are associated with more precise TMB estimated values 4,[62][63][64][65][66][67][68][69] Genes included in panel Gene selection in panels is biased toward frequently mutated cancerassociated genes, and mutation patterns of these genes are often nonrandom. 33 TMB scores may depend on whether the panel contains specific genes that harbor frequent mutations in specific tumor types…”
Section: Variation In Tmb Assessment and Factors That Impact Tmb Oumentioning
confidence: 99%
See 1 more Smart Citation